Path Analysis on the Organizational Factors Affecting Medical Service Quality and Patient Satisfaction at Dr. Moewardi Hospital, Surakarta - Riska Rosita; Bhisma Murti; Sumanto - (Masters Program in Public Health, Sebelas Maret University, 2016)
Background: Health service quality and patients satifaction are two important determinants for a hospital competitiveness. Patients always expect that the hospital provide good quality and satisfying service. This study aimed to determine the organizational factors that affect medical service quality and patient satisfaction at Dr. Moewardi Hospital, Surakarta.Subjects and Method: This was an analytical observational study using cross sectional design. This study was conducted at Dr. Moewardi Hospital, Surakarta, Indonesia, in November-December 2016. A total of 120 patients at Dr. Moewardi Hospital, were selected by stratified random sampling. The independent variables were personnel welfare, availability of facilities, and regulation of health care. The dependent variables were the quality of inpatient medical service and patient satisfaction. The data were collected by a questionnaire and analyzed by path analysis.Results: Personnel welfare (b=-0.13; p = 0.595) was not associated with the quality of medical service and patient satisfaction. Availability of facilities (b= size was 2.82; p = <0.001) had positive effect on the quality of medical care and patient satisfaction. Path analysis showed goodness of fit of the model, with CMIN = 4.35, p= 0.113, NFI = 0.99, CFI = 0.99, and RMSEA = 0.09.Conclusion: Personnel welfare and availability of facilities have positive effects on the quality of inpatient medical service and patient satisfaction.Keywords: Personnel welfare, availability of facility, quality of inpatient medical service, patient satisfaction, hospital.Correspondence: Riska Rosita. School of Medical Record, APIKES Citra Medika, Surakarta. Email: ross_rzkrosita@yahoo.comJournal of Health Policy and Management (2016), 1(2): 71-77https://doi.org/10.26911/thejhpm.2016.01.02.02